Valorizing Heritage and Cultural Identity from Land of Barsa through Cultural Tourism - BOTIȘ, Sorina (Journal of Environmental Management and Tourism; Vol 8 No 6 (2017): JEMT Volum VIII Issue 6(22) Fall 2017, 2018)
The purpose of the article is to initiate a research theme in the field of protecting and valorizing the national heritage and cultural identity, based on a series of arguments concerning the wide variety of resources belonging to the cultural heritage from Land of Barsa, variety which can become a stimulus for researchers, local public institutions or experts from abroad. The main aim of the research is to generate increased performances in this operational framework of valorization of the cultural heritage of Land of Barsa, increasing the quality of heritage sector through investments in conservation, training and an efficient and effective recovery of cultural tourism in this area. The research is divided in three stages, each of them with a clearly defined purpose and objective. The first stage is an evaluation of local heritage potential, the second stage is an evaluation of the satisfaction in term of valorizing material and intangible cultural heritage from Land of Barsa using a sample of 400 visitors and the third part formulates a plan for improving visitor satisfaction concerning the visitation experience, based on the results from the previous stages.